(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Chronic hepatitis B (CHB) remains a major global public health problem, leading to progressive liver disease, cirrhosis, and hepatocellular carcinoma. Long-term antiviral therapy with nucleos(t)ide analogues (NAs) is the cornerstone of CHB management, aiming to suppress hepatitis B virus (HBV) replication, prevent disease progression, and reduce liver-related complications. Despite proven antiviral efficacy, prolonged NA therapy raises concerns regarding drug resistance, safety, renal and bone toxicity, and long-term patient adherence. This study was conducted at the Khorezm Regional Multidisciplinary Medical Center and aimed to evaluate the safety and efficacy of long-term treatment with nucleos(t)ide analogues in patients with chronic hepatitis B. Patients were assessed based on virological, biochemical, and clinical parameters during extended antiviral therapy. The results demonstrate that long-term NA treatment effectively suppresses HBV replication, improves liver function, and is generally well tolerated, confirming the importance of continuous antiviral therapy in the management of chronic hepatitis B.